2009
DOI: 10.1007/s10822-009-9299-7
|View full text |Cite
|
Sign up to set email alerts
|

Homology modelling of the human adenosine A2B receptor based on X-ray structures of bovine rhodopsin, the β2-adrenergic receptor and the human adenosine A2A receptor

Abstract: A three-dimensional model of the human adenosine A2B receptor was generated by means of homology modelling, using the crystal structures of bovine rhodopsin, the beta2-adrenergic receptor, and the human adenosine A2A receptor as templates. In order to compare the three resulting models, the binding modes of the adenosine A2B receptor antagonists theophylline, ZM241385, MRS1706, and PSB601 were investigated. The A2A-based model was much better able to stabilize the ligands in the binding site than the other mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 63 publications
4
46
0
3
Order By: Relevance
“…Their results have suggested that to best exploit comparative models in molecular docking screens one should use consensus enrichment calculations that include multiple models as well as templates. Others have also addressed issues of docking into homology models (13,(15)(16)(17); for docking into homology models of G-Protein Coupled Receptors (GPCRs), see below.…”
Section: Receptor Representation In Docking Receptor Sourcementioning
confidence: 99%
“…Their results have suggested that to best exploit comparative models in molecular docking screens one should use consensus enrichment calculations that include multiple models as well as templates. Others have also addressed issues of docking into homology models (13,(15)(16)(17); for docking into homology models of G-Protein Coupled Receptors (GPCRs), see below.…”
Section: Receptor Representation In Docking Receptor Sourcementioning
confidence: 99%
“…The original 3D homology model of the human A 2B AR was based on the inactive, inverse agonist-bound A 2A AR (3EML) [15,16]. After exchange of the EL2 (the A 2B loop was exchanged for the A 2A loop) the model was energy-minimized again and subjected to molecular dynamics simulation as previously described [14].…”
Section: Homology Modelling and Dockingmentioning
confidence: 99%
“…This is particularly true for homology models of closely related receptor subtypes. One example is the A 2B adenosine receptor (A 2B AR) model [14,15], which has been constructed based on X-ray structures of the closely related A 2A AR [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The A 2B receptor encodes a protein of 328 to 332 amino acid residues depending on the species [Pierce et al, 1992]. As a result, a new and improved homology model for the human adenosine A 2B receptor was created and investigated [Sherbiny et al, 2009]. Consequently, virtual screening of potential ligands using the adenosine A 2B receptor model has been accomplished.…”
Section: (Figure 1)schematic Diagram Of a Gpcr With Seven Tm Domains mentioning
confidence: 99%
“…The protein target needs to be prepared and modeled according to the format requirements of the docking algorithms used. Thus the homology model of the human A 2B adenosine receptor [Sherbiny et al, 2009] was used. All bound water ligand were removed from the protein prior to the docking process…”
Section: Molecular Docking Proceduresmentioning
confidence: 99%